STUDIES ON CERTAIN GROWTH PARAMETERS OF DIFFERENT PROBIOTIC STRAINS - DUMITRA RĂDUCANU; ANA-MARIA GEORGESCU (Journal of Engineering Studies and Research)
The researchers found that probiotics contain microorganisms belonging to genus: Streptococcus, Lactobacillus, Bacillus, Aspergillus, Saccharomyces, Enterococcus, Pediococcus, enzymes (lactoperoxidase, gluconase, nonspecific enzymes) and rumen extracts. In this study, commercial probiotic bacteria known as "Linex" were used as samples. Cultural characteristics of these probiotic bacteria have been isolated and studied. It has been found that solid culture medium (nutritional gelose) favored the growth and development of bifidobacteria better than the liquid nutrient medium (nutrient broth). Thus, the number of bifidobacteria resulting from direct counting with Thoma chamber was of 7890 cells.